IMPLEMENTASI KONSEP LANGUAGE AWARENESS UNTUK MENINGKATKAN PENGUASAAN GRAMATIKAL BAHASA PRANCIS PADA MAHASISWA SASTRA PERANCIS FAKULTAS BAHASA DAN SENI UNIVERSITAS NEGERI SEMARANG - Yulianto, Ahmad; Sunahrowi, Sunahrowi (Jurnal Penelitian Pendidikan, 2016)
Most Indonesian learners are bilingual or even polyglot. Not only speaking their mother tongue (which is mostly regional language like Javanese or Sundanese), they are also exposed to foreign languages like Arabic, English and French. However, it does not necessarily means that learning foreign languages is easy for them. According to Chomsky, human beings are equipped with Language Acquisition Device which enables them to acquire any language they are exposed to. It is assumed that the more we are exposed to other languages, the easier it is for us to learn foreign languages. Communicative Approach is used in the learning process at Program Studi Sastra Perancis Universitas Negeri Semarang. This approach focuses on 4 competencies namely: Speaking (La production orale), Writing (La production ecrite), Listening Comprehension (La comprÃ©hension orale) and Reading Comprehension (La comprehension Ã©crite). Since Grammar Course has been abolished from the curriculum for a couple of years, it is in these 4 courses of competence that its teaching is integrated into. Unfortunately, most students are not quite competent in these four courses and also weak in Grammar. It is expected that Language Awareness concept help solve this problem.